Волшебный батик - Шилкова Елена Александровна (Школа рукоделия, 2012)
Экземпляры: аб. ДБ (20211122) / Инвентарный номер: 11685 / Цена: / Сис.шифр: Щ125 / Авт.знак: Ш 579 / ГРНТИ: 18.31.51 / ББК: 37.248